2004
DOI: 10.1109/ms.2004.1270766
|View full text |Cite
|
Sign up to set email alerts
|

Understanding service-oriented software

Abstract: I E E E P u b l i s h e d b y t h e I E E E C o m p u t e r S o c i e t y I E E E S O F T W A R E 7 1evolution. While they address some aspects of the problem, however, understanding the software still poses some difficulty. This shift toward service orientation compels us to consider its implications for software understanding, which is potentially the primary cost in software engineering. 2 Using an example of on-the-fly software services construction, we discuss the problems software engineers still face wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(69 citation statements)
references
References 6 publications
0
59
0
3
Order By: Relevance
“…With the fast advancement of the Web, SaaS applications conveyed as administrations through web turn into an important alternative of traditional software [2,3]. SaaS applications are conveyed in dynamic data centers [4] with distributed computing innovations overseeing assets to accomplish adaptability and scalability [5,6].…”
Section: Efficient Log Data Processing Management With the Concern Ofmentioning
confidence: 99%
“…With the fast advancement of the Web, SaaS applications conveyed as administrations through web turn into an important alternative of traditional software [2,3]. SaaS applications are conveyed in dynamic data centers [4] with distributed computing innovations overseeing assets to accomplish adaptability and scalability [5,6].…”
Section: Efficient Log Data Processing Management With the Concern Ofmentioning
confidence: 99%
“…But this flexibility may create significant problems when the composite application needs to evolve. Several authors have pointed out characteristics of SOA that may make such maintenance difficult [3][4] [9]. An important part of any maintenance task is acquiring the knowledge needed to make changes to the software; changes made based on incomplete understanding may fail with disastrous results.…”
Section: O P Y R I G H T © S O C I E T Y F O R S C I E N C E a N D mentioning
confidence: 99%
“…Such systems present several software engineering challenges because they need to orchestrate diverse services having different owners, and have complex reliability requirements. While developing SOA applications presents many software engineering challenges, managing the evolution of such systems presents even greater challenges [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…When the software that's made available as a service is a database system, the model is often labeled as Database-as-a-Service (DaaS). From an historical research perspective, it is important to recognize that early visions of turning software into a service (Turner et al, 2003) suggested use of multiple low-level services and providing a larger service using SOA (Gold et al, 2004;Papazoglou, 2003). But when considered today, SaaS is generally a single ASP product with little integration with other open services (Sun et al, 2007;Wei & Blake, 2010) and sometimes deliberately as walledgardens to cause lock-ins (Cerbo et al, 2012).…”
mentioning
confidence: 99%